2010
DOI: 10.1111/j.1600-051x.2010.01578.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non‐surgical periodontal therapy on the glomerular filtration rate of the kidney: an exploratory trial

Abstract: GFR, as assessed by cystatin C levels, may be positively affected by PT. Because of the exploratory nature of this trial, further research is needed to investigate this preliminary finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(100 citation statements)
references
References 48 publications
4
96
0
Order By: Relevance
“…This difference may be explained by the following: most of the patients had mild to moderate severity which required only non-surgical therapy; there were no reports of events that affected systemic inflammation during the study; and most of the other previous studies did not demonstrate serial marker monitoring data, especially in the hemodialysis patients. Regarding evidence from non-chronic kidney disease patient, Graziani et al 50,51 reported that serum inflammatory markers showed an evident increase 1 day after treatment, and the values were reverted to baseline values at 7 days. From the nutritional aspect, we not only found significant negative correlation between hs-CRP and nutritional parameters (albumin and nPCR), which may be explained by the fact that pro-inflammatory cytokines could adversely affect nutrition by inducing proteolysis in muscle, increasing energy expenditure, and inhibiting appetite, but also demonstrated improvement in the nutritional parameter.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be explained by the following: most of the patients had mild to moderate severity which required only non-surgical therapy; there were no reports of events that affected systemic inflammation during the study; and most of the other previous studies did not demonstrate serial marker monitoring data, especially in the hemodialysis patients. Regarding evidence from non-chronic kidney disease patient, Graziani et al 50,51 reported that serum inflammatory markers showed an evident increase 1 day after treatment, and the values were reverted to baseline values at 7 days. From the nutritional aspect, we not only found significant negative correlation between hs-CRP and nutritional parameters (albumin and nPCR), which may be explained by the fact that pro-inflammatory cytokines could adversely affect nutrition by inducing proteolysis in muscle, increasing energy expenditure, and inhibiting appetite, but also demonstrated improvement in the nutritional parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Greater increase of C-reactive protein (CRP) and Serum Amyloid A (SAA) was observed in the first 24 hours and decreased after 30 days of treatment. Periodontal infection with intensive therapy may increase endothelial function and may reduce systemic inflammatory markers acting on the risk of serious diseases [15]. The kinetics of serum inflammatory markers are observed after a course of treatment comprising surgical and non-surgical treatment of chronic periodontitis (CP) and found marked increase in serum levels of CRP and SAA in 24 hour after non-surgical therapy and periodontal surgeries [16].…”
Section: Serum Amyloid-amentioning
confidence: 99%
“…Fibrinogen showed mild increase in the first 24 hours of non-surgical periodontal therapy and normalized after 30 days [15].…”
Section: Fibrinogenmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Artese HP et al 23 found that CKD predialysis patients show a good response to nonsurgical periodontal treatment with statistically significant improvement in GFR indicating improved renal health. Fillippo Graziani et al 29 described the kinetics of serum inflammatory markers after a course of treatment comparing surgical and nonsurgical treatments for chronic periodontitis. The results concluded that patients undergoing periodontal treatment experience perturbations of systemic inflamma tion of a greater magnitude after nonsurgical than surgical periodontal therapy.…”
Section: Resultsmentioning
confidence: 99%